2009
DOI: 10.19030/ajbe.v2i9.4613
|View full text |Cite
|
Sign up to set email alerts
|

Changing The Culture Of A School: The Effect Of Larger Class Size On Instructor And Student Performance

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Across all departments, there was a significant drop in the number of responses. However, analysis of the results showed that there was no significant difference in the paper and online values given to courses or faculty for whom evaluations existed in both paper and online formats (Guder et al, 2009). However, with the online evaluations, the response rate dropped by 26% on the undergraduate level (Guder & Malliaris, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Across all departments, there was a significant drop in the number of responses. However, analysis of the results showed that there was no significant difference in the paper and online values given to courses or faculty for whom evaluations existed in both paper and online formats (Guder et al, 2009). However, with the online evaluations, the response rate dropped by 26% on the undergraduate level (Guder & Malliaris, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Many professors believe that the students enrolled in remedial courses are not ready for college and therefore should not be enrolled at the university. Full-time professors often avoid teaching developmental or freshmen-level courses, as they are usually larger in class size and the students who take these courses tend to submit lower teacher evaluation scores (J. Baglama, personal communication, January 23, 2015; Barth, Liu, & Wells, 2009;Feldman, 1984;Guder, Malliaris, & Jalilvand, 2011). Since senior faculty members have more input regarding the classes they teach, graduate students or adjunct faculty members generally teach these developmental courses.…”
Section: Common Principles Perceptions and Practices In College Matmentioning
confidence: 99%
“…Further, some professors claim that students score professors more favorably on the evaluations if the course is easier, the instructor holds lower expectations, or if the instructor cancels class frequently (Barth et al, 2009;Guder et al, 2011). Professors Michael Barth, Jun Liu, and William Wells reported that "there often is a perception that rigorous academic standards lower student evaluations of teaching" (Barth et al, 2009, p. 94).…”
Section: Current Practices In Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…As pressures mount for larger class sections in higher education (Guder, Malliaris, & Jalilvand, 2009;Thanopoulos, 2004), conducting oral exams with each student is more challenging, especially if competent teaching assistants are unavailable. Administering oral exams in the online educational environment might also prove unworkable, although possible, via Skype or other technologies.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%